Identification of Faecalibacterium prausnitzii strains for gut microbiome-based intervention in Alzheimer’s-type dementia - Ueda, Atsushi; Shinkai, Shoji; Shiroma, Hirotsugu; Taniguchi, Yu; Tsuchida, Sayaka; Kariya, Takahiro; Kawahara, Tomohiro; Kobayashi, Yodai; Kohda, Noriyuki; Ushida, Kazunari; Kitamura, Akihiko; Yamada, Takuji (Cell reports. Medicine, 2021)
Evidence linking the gut-brain axis to Alzheimer’s disease (AD) is accumulating, but the characteristics of causally important microbes are poorly understood. We perform a fecal microbiome analysis in healthy subjects and those with mild cognitive impairment (MCI) and AD. We find that Faecalibacterium prausnitzii (F. prausnitzii) correlates with cognitive scores and decreases in the MCI group compared with the healthy group. Two isolated strains from the healthy group, live Fp360 and pasteurized Fp14, improve cognitive impairment in an AD mouse model. Whole-genome comparison of isolated strains reveals specific orthologs that are found only in the effective strains and are more abundant in the healthy group compared with the MCI group. Metabolome and RNA sequencing analyses of mouse brains provides mechanistic insights into the relationship between the efficacy of pasteurized Fp14, oxidative stress, and mitochondrial function. We conclude that F. prausnitzii strains with these specific orthologs are candidates for gut microbiome-based intervention in Alzheimer's-type dementia. [Display omitted] F. prausnitzii decreases in subjects with MCI and correlates with cognitive test scoresIsolated F. prausnitzii strains improve Aβ-induced cognitive impairment in miceComparative genomics reveals specific orthologs in the effective strainsEffects of F. prausnitzii relate to oxidative stress and mitochondrial function Ueda et al. observe a reduction of F. prausnitzii in volunteers with MCI and show that isolated F. prausnitzii strains from healthy volunteers improve cognitive impairment in mice. Using integrated whole-genome and metagenome analyses, they identify F. prausnitzii strains with specific orthologs as candidates for gut microbiome-based intervention in AD.